2008
DOI: 10.1371/journal.pone.0003930
|View full text |Cite|
|
Sign up to set email alerts
|

Settling Decisions and Heterospecific Social Information Use in Shrikes

Abstract: Animals often settle near competitors, a behavior known as social attraction, which belies standard habitat selection theory. Two hypotheses account for these observations: individuals obtain Allee benefits mediated by the physical presence of a competitor, or they use successfully settled individual as a source of information indicating the location of high quality habitat. We evaluated these hypotheses experimentally in two species of shrikes. These passerine birds with a raptor-like mode of life impale prey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 37 publications
1
41
0
1
Order By: Relevance
“…Third, the presence of residents can be a signal of low risk of predation, as the residents may already have been predated in patches with a higher predation risk. Heterospecifics can also act as indicators of habitat quality, especially for migrant species arriving to breeding sites (Thomson et al 2003;Forsman & Thomson 2008;Hromada et al 2008;Forsman et al 2009). Migrants need to make fast but reliable decisions about where to breed, whereas residents have had much more time to evaluate patch quality.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the presence of residents can be a signal of low risk of predation, as the residents may already have been predated in patches with a higher predation risk. Heterospecifics can also act as indicators of habitat quality, especially for migrant species arriving to breeding sites (Thomson et al 2003;Forsman & Thomson 2008;Hromada et al 2008;Forsman et al 2009). Migrants need to make fast but reliable decisions about where to breed, whereas residents have had much more time to evaluate patch quality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mate-choice copying (a form of social information use) was demonstrated in wild sailfin mollies (Poecilia latipinna), but the design did not incorporate a subsequent phase without demonstrators to test whether any learning had taken place (Witte & Ryan, 2002). Similarly, Hromada, Antczak, Valone, and Tryjanowski (2008) demonstrated that male red-backed shrikes (Lanius collurio ( ( ) used the social information provided by food caches (impaled prey, artifacts of successful foraging) in making settlement decisions, but the authors did not observe behavior in the absence of the caches. We suspect that learning is likely in such cases, but it was not formally demonstrated.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Thus, tradition-defined as the transfer of any kind of information between individuals and species (Avital and Jablonka 2001;Danchin et al 2004;Fragaszy and Perry 2003;Hromada et al 2008)-may play a major role in habitat and (particularly) nest-site choice of many species, and appears to be an underrated mechanism. In line with this, the main route for information transfer is from parents to offspring, so habitat imprinting would be a suitable mechanism for nest-site selection in birds (Glück 1984;Teuschl et al 1998).…”
Section: Introductionmentioning
confidence: 99%